3-Amino-4-hydroxybenzoic acid production from sweet sorghum juice by recombinant Corynebacterium glutamicum. (December 2015) - Kawaguchi, Hideo; Sasaki, Kengo; Uematsu, Kouji; Tsuge, Yota; Teramura, Hiroshi; Okai, Naoko; Nakamura-Tsuruta, Sachiko; Katsuyama, Yohei; Sugai, Yoshinori; Ohnishi, Yasuo; Hirano, Ko; Sazuka, Takashi; et al.
Highlights: The stalk juice of sweet sorghum contained fermentable sugars and amino acids. Recombinant Corynebacterium glutamicum produced 3, 4-AHBA from sorghum juice. Components of sweet sorghum juice were fractionated by membrane separation. Amino acids of Leu or Cys in sweet sorghum juice enhanced 3, 4-AHBA production. Abstract: The production of the bioplastic precursor 3-amino-4-hydroxybenzoic acid (3, 4-AHBA) from sweet sorghum juice, which contains amino acids and the fermentable sugars sucrose, glucose and fructose, was assessed to address the limitations of producing bio-based chemicals from renewable feedstocks. Recombinant Corynebacterium glutamicum strain KT01 expressing griH and griI derived from Streptomyces griseus produced 3, 4-AHBA from the sweet sorghum juice of cultivar SIL-05 at a final concentration (1.0 g l −1 ) that was 5-fold higher than that from pure sucrose. Fractionation of sweet sorghum juice by nanofiltration (NF) membrane separation (molecular weight cut-off 150) revealed that the NF-concentrated fraction, which contained the highest concentrations of amino acids, increased 3, 4-AHBA production, whereas the NF-filtrated fraction inhibited 3, 4-AHBA biosynthesis. Amino acid supplementation experiments revealed that leucine specifically enhanced 3, 4-AHBA production by strain KT01. Taken together, these results suggest that sweet sorghum juice is a potentially suitable feedstock for 3, 4-AHBA production by recombinant C. glutamicum .